Pelapis Cat Hitam Pada Penggunaan Penutup Atap Seng Sebagai Perbandingan Suhu Dalam Ruang - Frumensia, Silfira; Setiadi, Imelda; Putra, Heristama Anugerah (Jurnal Lingkungan Karya Arsitektur, 2024)
The roof covering must have the function of protecting the building from weather or other disturbing and dangerous objects. Apart from that, the roof also has the function of influencing the temperature and humidity in an area within a space. There are various types of roofs that can be applied to various buildings, one of which is the tin roof. This research was carried out using quantitative methods in the form of experiments or trials using room temperature applications on the ability of roof coverings to withstand solar heat. Measurements are made by comparing the temperature between tin roofs that are coated with black paint and zinc that is not coated with black or a neutral color according to the color of the original material. The aim of this research is to determine the temperature comparison of the interior of zinc whose surface is coated with black paint and zinc that is not coated with black paint. According to calculations through these observational experiments, black paint on the surface of a tin roof that is given black paint is able to reduce heat, even though black itself is a color that absorbs more heat than other colors. So that zinc coated with black paint is able to make the indoor temperature lower compared to zinc roofing material that is not coated with black paint.